Cerebral areas affected by unilateral acupuncture on SP3 in healthy volunteers: An explorative resting‐state fMRI study. Issue 4 (9th February 2021) - Wang, Feng; Yang, Tiansong; Li, Xiaoling; Liu, Xiaohui; Cao, Danna; Wang, Delong; Yang, Yan; Li, Chaoran; Qu, Yuanyuan; Zhao, Xu; Sun, Zhongren; Asakawa, Tetsuya
Abstract: Objective: The study aimed to explore the cerebral areas with changes in regional homogeneity (ReHo) and amplitude of low‐frequency fluctuation (ALFF) values induced by effective acupuncture on the Taibai (SP3) point. Methods: In the study, 15 healthy right‐handed volunteers (seven males and eight females, 20–35 years old) were enrolled. The average ages of the subjects were 28.0 ± 4.24 years for males and 27.4 ± 3.65 years for females. A 3.0T magnetic resonance imaging (MRI) system was used to perform resting‐state functional MRI scan after sham and effective acupuncture on the SP3 point. The differences in cerebral ReHo and ALFF values between posteffective acupuncture and postsham acupuncture were compared using the SPM 12 software. Results: ReHo values of bilateral BA18, cuneus, and BA17, along with BA41, BA22, postcentral gyrus, and BA7 on the right side, were decreased by effective SP3 acupuncture. The ALFF values of bilateral BA 30 and left parahippocampal area were increased, whereas the values of bilateral BA18, BA19, cuneus, posterior cingulate gyrus, and BA7, along with the right superior occipital lobule, postcentral gyrus, and left precuneus, were decreased. Conclusions: The most dominant cerebral areas affected by SP3 acupuncture were bilateral visual‐related cortices (lingual gyrus, cuneus, and calcarine), along with the unilateral postcentral gyrus and superior parietal lobule. These findings may be potential explanations for the available clinical reports concerning the efficacy of SP3 acupuncture. Further clinical and experimental studies on SP3 acupuncture are required. Abstract : This is the first study to explore the cerebral areas with changes in ReHo and ALFF values induced by acupuncture on the SP3 point (Taibai).This paper contributes to the understanding of the physiological effects of SP3 acupuncture.